Localized mycosis fungoides treated with laser‐assisted photodynamic therapy: a case series. (1st March 2019) - Dairi, M.; Dadban, A.; Arnault, J.‐P.; Lok, C.; Chaby, G.
Abstract : Click here for the corresponding questions to this CME article.